2022
DOI: 10.5430/jnep.v13n1p31
|View full text |Cite
|
Sign up to set email alerts
|

First-year nursing students’ digital literacy: A cross-sectional study

Abstract: Background: The digital world is rapidly changing, and so do the required digital skills. As physical devices and software are adapted to meet new possibilities and demands, individuals’ skills must adapt to technological advancement. Digital literacy is increasingly used in the public discourse, becoming a core requirement of students, academics, patients and healthcare professionals. Assessing nursing students’ digital literacy at the entry-level is vital to ascertain their abilities to use digital technolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 33 publications
2
9
0
2
Order By: Relevance
“…This could be related to the resources available in each region. Such a finding was similar to the results of a previous study that students from urban areas were more digitally skilled than those from rural and semi-urban areas [13].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This could be related to the resources available in each region. Such a finding was similar to the results of a previous study that students from urban areas were more digitally skilled than those from rural and semi-urban areas [13].…”
Section: Discussionsupporting
confidence: 91%
“…Digital competence goes beyond operational skills and knowledge about how to use a certain technology [13,35]. Our results demonstrated that students have a high level of engagement in various digital activities during their study period following JISC's framework [13,15,36]. Superior results are seen for digital learning and development, in which participating nursing students seem competent in everyday digital literacy such as accessing learning resources.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations